A new proposal for the distinction between lexical and syntactic derivation in Functional Discourse Grammar. (March 2018) - Muñoz, Carmen Portero; Velasco, Daniel García
Abstract : This paper explores the possibility of classifying traditional affixes as two groups, syntactic or lexical affixes, as proposed within Functional Discourse Grammar (FDG). It is argued that the main challenge for the FDG approach to derivational morphology arises from properties which revolve around the semantic contribution of derivational affixes: i) the fact that derivational processes introduce unpredictable meaning components (semantic opacity), ii) the question of what constitutes lexical meaning vs. grammatical meaning, iii) the intrinsic polysemy of some affixes, and iv) affix competition. The authors conclude that FDG should treat lexical and grammatical affixes similarly, unless a clear distinction can be made in particular cases on clearly specified semantic principles.